A review on the use of waste plastics in hot mix asphalt - Mehta D.; Saboo N.; Abraham S.M.; Diwaker U. (My University, 2025)
Amongst various avenues being searched for solving the menace of increasing amount of plastic accumulation, its use in hot mix asphalt (HMA) is becoming popular. Several research studies have been conducted since the 1980s on the use of different types of waste plastics in asphalt mixtures through dry and wet processes. While it may seem ‘simple’ and ‘attractive’, incorporation of waste plastic in asphalt mixtures is plagued with many challenges. This paper summarizes the works of the available literature on the use of waste plastics in asphalt mixture. The selection of dry or wet process is highly dependent on type, density, size and melting point of waste plastic, to create a homogeneous mixture. Physical, rheological, and morphological properties of asphalt binder are effectively altered by the use of waste plastics. This is in turn is a function of various parameters such as type of plastic and base asphalt binder, dosages used, use of compatibilizers and other polymers, production process, etc. Similarly, the performance of waste plastic modified asphalt mixture is found to vary considerably. While the stiffness characteristics of HMA is improved by incorporation of waste plastic, more studies on in-field performance and environmental concerns are desirable. To make the use of waste plastic in HMA a ‘success story’, there is a need to carry out fundamental research to generate a unified solution. © The Author(s), under exclusive licence to Springer Nature B.V. 2023.